(untitled) (Global Journal of Management and Business Research, 2023)
The primary objective of this study is to enhance the comprehension of the obstacles and achievements faced by self-initiated expatriates residing in the United States By employing in-depth interviews this study examines the intricate experiences of individuals who have engaged in self-initiated expatriation thereby providing insights into the challenges and opportunities encountered by organizations operating in this particular context Through the utilization of a qualitative methodology the study captures the multifaceted narratives and distinct viewpoints of the participants thereby unraveling the intricate intricacies of their individual journeys This provide valuable insights into the complex relationship between individuals and organizations in the context of self-initiated expatriation This was achieved through the use of thematic analysis The results of the study emphasize that self-initiated expatriates possess distinctive abilities and viewpoints presenting a valuable asset for organizations seeking to improve innovation and adaptability The research highlights examples in which organizations effectively leverage the capabilities of Social Impact Enterprises attaining a synergistic equilibrium between centralized global oversight and individual independence This research makes a valuable contribution to the fields of expatriation by examining the challenges faced by self-initiated expatriates in the United States